The perversion of local novel morality and its implementation of learning faces a demographic bonus - Deri Wan Minto; Ananda Putriani; Sri Wahyuni; Eleonor Francisco (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2024)
The background is based on the phenomenon of deviating aspects of morality which often color Minangkabau novels. As a result, there are writers who criticize especially social problems that occur in local communities. The purpose of this research is to describe aspects of deviating aspects of morality in local novels, especially Ismet Fanany's Bulan Susut by Ismet Fanany and their implementation towards learning in schools in the face of the demographic bonus era. Qualitative and analytical descriptive methods form the basis of this research type and method. Based on the findings (1) Aspects of conscience with a total of 9 data findings with a percentage of 21.96%. (2) Aspects of freedom and responsibility with a total of 11 data findings with a percentage of 26.83%. (3) Aspects of rights and obligations with a total of 8 data findings with a percentage of 19.51%. (4) Aspects of values and norms with a total of 13 data findings with a percentage of 31.70%. Implications in this research are interpreted not to be taught research that is obtained openly which is direct in nature, but this research will utilize positive values as an effort to form good character for learning challenges in the era of demographic bonuses.